Dosimetry and cost of imaging osseointegrated implants with film-based and computed tomography - Scaf, Gulnara [UNESP]; Lurie, Alan G.; Mosier, Kristine M.; Kantor, Mel L.; Ramsby, Gale R.; Freedman, Michael L. (Elsevier, 1997)
Thermoluminescent dosimeters were used to measure radiation doses at craniofacial sites in a tissue-equivalent phantom during film-based multidirectional tomography with the Tomax Ultrascan (Incubation Industries, Ivyland, Pa.) and during computed tomography with the Elscint Excel 2400 (Elscint Corp., Tel Aviv, Israel). Mean absorbed doses for presurgical mandibular and maxillary canine and molar implant assessments were converted to equivalent doses, which were then multipied by published weighting factors and summed to give effective doses. The computed tomgraphy device consistently delivered higher doses than the Tomax Ultrascan to all anatomic locations; the differences were most pronounced when only one or two implant sites were evaluated. The reasons for the dose disparities are considered both anatomically and procedurally. A survey of examination cost revealed film-based multidirectional tomography to be less expensive than computed tomography.